Microstructural evolutions and mechanical characteristics of Ti/steel clad plates fabricated through cold spray additive manufacturing followed by hot-rolling and annealing. (5th January 2020) - Zhao, Zhipo; Tariq, Naeem ul Haq; Tang, Junrong; Jia, Cunlei; Qiu, Xiang; Ren, Yupeng; Liu, Hanhui; Shen, Yanfang; Du, Hao; Cui, Xinyu; Wang, Jiqiang; Xiong, Tianying
Abstract: An innovative approach is designed to fabricate Ti/steel clad plates. Instead of using Ti sheets, pure Ti powder was initially deposited on steel plates using cold spray additive manufacturing (CSAM). Then well bonded Ti/steel clad plates were obtained through hot-rolling and annealing operations. The mechanical properties of the clad plates at different processing stages were evaluated by performing a series of tensile tests and shear tests. It was revealed that the Ti/steel clad plates had excellent shear strength (280 Mpa), ultimate tensile strength (UTS, 564 Mpa) and decent elongation (EL, 18%). Microstructural investigation of the specimens was performed by scanning electron microscopy (SEM), electron backscattered diffraction (EBSD) and transmission electron microscopy (TEM). It was revealed that cold spraying offers good pre-bonding of Ti with the steel plate thereby suppressing cracking and oxidation at the interface. Hot-rolling treatment repaired the pores/defects in the as-sprayed Ti coating and resulted in metallurgical bonding between Ti particles as well as Ti/steel interface, which remarkably improved the strength of the material. High dislocation density in the clad plates were further eliminated by the annealing treatment through recovery, recrystallization and grain growth mechanisms, which greatly improved the toughness of the samples. Graphical abstract: Image 1 Highlights: Ti/steel clad plates were fabricated via cold spray additive manufacturing followed by hot rolling and annealing co-treatments. The Ti/steel clad plates show excellent tensile strength, elongation and shear strength. Cold spray resulted in pre-bonding of the Ti/steel interface and inhibition of oxidation at the interface. Hot rolling repaired the defects and resulted in metallurgical bonding of Ti/steel （Ti/Ti） interface. Annealing led to recovery and recrystallization, which resulted in increased toughness.